Assessment of fatigue response of thermally aged reduced activation ferritic-martensitic steel based on finite element analysis. (3rd March 2016) - Goyal, Sunil; Veerababu, J.; Prasad Reddy, G. V.; Sandhya, R.; Laha, K.
Abstract: In the present investigation, effect of thermal ageing on low cycle fatigue (LCF) behaviour of Reduced Activation Ferritic Martensitic steel has been assessed by finite element analysis. The steel was thermally aged at 873 K for 3000 hour. Low cycle fatigue tests were carried out on both the as-received and thermally aged material at strain rate of 3×10 −3 s −1 at 823 K, over strain amplitudes in the range of ± 0.25 to ± 0.8%. Continuous cyclic softening till final failure, except for initial few cycles especially at relatively lower strain amplitudes, was observed in both the material conditions. Thermal ageing resulted in marginally higher cyclic stress response accompanied by lower fatigue life. The differences in fatigue responses have been attributed to the coarsening of precipitates on thermal ageing. Finite element analysis has been carried out considering combined isotropic and kinematic hardening as material model to estimate the effect of thermal ageing on the response of material under LCF loading. Thermal ageing was found to decrease both the isotropic and kinematic hardening with appreciable effect on isotropic hardening. The predicted cyclic stress response and hysteresis loops were found to be in good agreement with the experimental data. The LCF life of the steel has been estimated based on the hysteresis energy approach.